Cross-listing and liquidity in emerging market stocks - Silva, Ana Cristina; Chávez, Gonzalo A. (Journal of Banking & Finance, 2008)
In this study, we analyze liquidity costs for stocks and ADRs from the four main Latin American markets. The results indicate that international investors are exposed to different trading costs in Latin America, with market location and firm size as important determinants. In the local market, stocks that cross-list internationally do not always present a liquidity cost advantage relative to non-cross-listed stocks. When the ADR and the local stock markets are compared, large firms present lower trading costs in the home market. The opposite occurs for small firms.